The trickle-down effects of creative work involvement: The joint moderating effects of proactive personality and leader creativity expectations. (1st May 2019) - Zhao, Hongdan; Guo, Limin
Abstract: This study aims to examine the effect of leaders' creative work involvement on employees' creative work involvement by specifically focusing on the joint moderating effects of proactive personality (individual differences) and leader creativity expectations (social contexts). The results of a hierarchical regression analysis using a sample of 138 employee-colleague dyads from a company in mainland China showed that as predicted, leaders' creative work involvement was positively related to employees' creative work involvement. Moreover, the findings indicated that high proactive personality coupled with low leader creativity expectations led to the strongest relationship between leaders' creative work involvement and employees' creative work involvement, while low proactive personality combined with low leader creativity expectations resulted in the weakest relationship between leaders' creative work involvement and employees' creative work involvement. Our study contributes to the creative work involvement literature by investigating the important role of leaders' creative work involvement for employees' creative work involvement, and clarifying when and why employees are more fully involved in creative efforts. Highlights: Examines the trickle-down effects of creative work involvement Proactive personality and leader creativity expectations jointly moderate the link. Uses the self-determination theory as the theoretical base